Implementation of Improving Digital Literacy Skills Through The Literacy-Cloud Platform for Attention Deficit Hyperactivity Disorder (ADHD) Learners in Inclusive Schools - Khair, Abdul; Murtadlo, Murtadlo; Purbaningrum, Endang (Department of Special Education, 2023)
The purpose of this research is: 1) To foster a reading or literacy culture 2) To practice enjoyable reading activities 3) To implement reading or literacy activities for students with ADHD. 4) To assist in the registration of Literacy-Cloud platform accounts for teachers and students with ADHD. The research is conducted at SD Labschool UNESA with a population of 12 classes and a sample size of 6 students with ADHD who experience difficulties in focusing on objects or reading materials. The enhancement of digital literacy skills through the Literacy-Cloud Platform, as a movement to motivate, engage, and cultivate digital reading culture, using a participatory persuasive approach. The method used is qualitative descriptive with data sources consisting of interview results, literature review, field notes, and observation results. This activity consists of three treatments: training, assistance with digital information search strategies, and the implementation of enjoyable reading for the students. This program has successfully improved the digital literacy of teachers and students, especially students with ADHD. Evaluation results show that teachers and students are able to search for digital reading materials and apply enjoyable reading practices to the students.